144k views
5 votes
5(2k - 3 )-3(k+4)/ 3k+2; k= -2

2 Answers

4 votes

Answer:

-33

Explanation:

5(2k - 3 )-3(k+4)/ 3k+2

5(2*(-2)-3)-3((-2)+4)/3*(-2)+2

5(-4-3)-3(2)/(-6)+2

5(-7)-6/(-6)+2

-35+1+2

-33

User Sbabti Zied
by
6.5k points
3 votes

Answer:

First, we substitute k=-2 in the given expression and we calculate the numerical value.


(5(2k-3)-3(k+4)/(3k+2) =(512(-2)-3](-2+4)/(3(-2)+2)


=(5(-4-3)-3(2))/(-6+2)


=(5(-7)-6)/(-4)


=(-41)/(-4)


=(41)/(4)

OAmalOHopeO

User Dbyrne
by
6.0k points